ICWSM 2020 spotlight paper - Sirivianos, Michael; Papadamou, Kostantinos (My University, 2026)
International AAAI Conference on Web and Social Media (ICWSM) spotlight paper (top 8 out of 70+) https://www.icwsm.org/2020/
Keywords: Sciences